Relationship Marketing and Customer Retention - A Systematic Literature Review - Rosário, Albérico; Casaca, Joaquim A. (Studies in business and economics (Romania), 2023)
Relationship marketing is the process of establishing, maintaining, and improving solid relationships with a company’s customers and other stakeholders. Relationship marketing can significantly impact customer satisfaction, trust, commitment, and communication, which are critical in customer retention and increasing the probability of using a company’s products or services in the future. With globalization and technological advancements, competition and consumer demands have become more complicated, prompting firms to employ strategies that strengthen customer loyalty and trust for long-term relationships. This paper aims to identify research trends in the field through a systematic bibliometric literature review of research on relationship marketing and customer retention. The review includes 61 articles published in the Scopus® database, presenting up-to-date knowledge on the topic. The bibliographic search included peer-reviewed articles published up to 2022. The findings indicate that relationship marketing provides a win-win solution: customers benefit from special and unique treatment under relationship marketing, and companies benefit from stronger customer relationships that eventually translate to higher profitability and performance in target markets’ marketing initiatives. Relationship marketing produces multiple opportunities and benefits that facilitate the creation, maintenance, and improvement of customer retention programs.